Pengaruh Pariwisata Terhadap Perekonomian Lokal di Kawasan Wisata Pantai - Ulfa Setyaningsih (Lembaga Penelitian dan Pendidikan, 2025)
Tourism development has been recognized as a key driver of economic growth in coastal regions. This study aims to analyze the impact of tourism on the local economy in coastal tourist areas, focusing on the Senggigi Beach area in Lombok, Indonesia. A mixed-methods approach was employed, combining survey data from local business actors and residents with secondary data on tourism statistics. The results show that tourism contributes significantly to employment creation, local income enhancement, and the development of small and medium-sized enterprises. However, challenges such as income inequality, seasonal economic fluctuations, and environmental degradation were also identified. This study provides practical implications for policymakers to strengthen sustainable tourism strategies that balance economic benefits with social and environmental considerations.